Bacterial Vaginosis and Sexually Transmitted Infections in an HIV-Positive Cohort - Nava-Memije, Karina; Hernández-Cortez, Cecilia; Ruiz-González, Verónica; Saldaña-Juárez, Claudia A.; Medina-Islas, Yazmín; Dueñas-Domínguez, Roberto A.; Aguilera-Arreola, Ma. Guadalupe (Frontiers in Reproductive Health, 2021)
The World Health Organization and the Joint United Nations Programme on HIV and AIDS (UNAIDS) suggest that sexually transmitted infection (STI) surveillance should include other genital infections and not only HIV. To monitor the concomitance of BV and sexually transmitted infections in HIV-seropositive and HIV-seronegative patients, a prospective study was conducted in a cohort of 349 volunteers at a clinic specializing in treating sexually transmitted infections in Mexico City. Microbiological and molecular methods were used to detect STIs and dysbiosis in PHIV+ and PHIV- individuals. The prevalence of infection was higher in PHIV+ (69.28%) than in PHIV- (54.87%). Bacterial vaginosis was the most frequent infection in PHIV+ individuals, and polymicrobial infections were three times more common in PHIV+ individuals than in PHIV- individuals (31.48% vs 10.98%). The behaviour documented in a self-administered questionnaire shows low condom use frequency in PHIV+ volunteers co-infected with BV or STI. This finding highlights the importance of surveillance using routine microbiological evaluations for the correct management of genital infections in PHIV+ patients because in the presence of HIV, the clinical presentation, course, and therapeutic response of some sexually transmitted infections can be different to those inpatients without HIV infections.